The Combined Use of Groundwater Quality, Drawdown Index and Land Use to Establish a Multi-Purpose Groundwater Utilization Plan - Liang, Ching-Ping; Hsu, Wen-Shuo; Chien, Yi-Chi; Wang, Sheng-Wei; Chen, Jui-Sheng (Water resources management, 2019)
Groundwater is abundant and widely used for household consumption, irrigation, and aquaculture in the Lanyang Plain in northeastern Taiwan. However, it is subject to contamination by various anthropogenic activities and natural processes, as well as overexploitation, which has led to land subsidence in the eastern coastal area of this plain. It is becoming increasingly urgent to establish a sound plan for groundwater resource management in the Lanyang Plain to ensure the safe and sustainable use of groundwater to meet demands. The aim of this study is to develop a sound management plan for multipurpose groundwater utilization in the Lanyang Plain. This plan is developed with consideration of the quality and quantity of groundwater, as well as current land use practices. First, the groundwater quality parameters are spatially mapped followed by geographic determination of regions where groundwater quality is safe for different purposes, based on the water quality criteria for drinking, irrigation, and aquaculture. Subsequently, the drawdown index, defined as the ratio of the actual groundwater utilization rate to the transmissivity, is determined for each cell and low drawdown index regions are identified geographically. Information about regions where groundwater quality is safe for different purposes and the regions where the drawdown index is low is integrated to create a map which can be used for the production of a sound management plan for multi-purpose groundwater utilization in the Lanyang Plain. Comparisons between our newly created map and current land use for farmlands and fishponds can provide a basis to review the current land use practices in these regions.